PENGEMBANGAN APLIKASI PENJADWALAN KONTEN INSTAGRAM OTOMATIS BAGI PELAKU UMKM DENGAN FLUTTER FRAMEWORK - Chrystian Dwi Putra Yunus; Muhamad Bahrul Ulum (JURNAL ILMIAH INFORMATIKA, 2023)
The actors Micro, Small, and Medium Business (MSMEs) which are dominated by the elderly, still rely on conventional marketing (mouth to mouth), resulting in a small market. In this condition, digital marketing is here to be a solution, where MSMEs have great potential to develop their market without any geographical restrictions. However, most of these MSMEs are not young anymore, making it difficult for them to adapt to digital technology. One of them is Instagram (social media) which has great potential in digital marketing. Therefore, in this study, an application will be developed using Flutter Framework that can help MSME actors to be able to automatically generate an Instagram content schedule according to the intensity level of Instagram promotions and features they want to use. So that it can help them in optimizing digital marketing without the need to adapt to social media that tends to make it difficult for them.